Leaf and stem anatomical traits of Muntingia calabura L. (Muntingiaceae) emphasizing the production sites of bioactive compounds - Seixas, Diana Pacheco [UNESP] (2021)
Muntingia calabura L. is a neotropical Muntingiaceae tree with medicinal properties and economic interest. Extracts from its leaves and stems are rich in carbohydrates, volatiles and phenolic compounds with proved anti-tumor, antinociceptive and thermogenic properties. However, little is known about the structural features of leaves and stem and where these compounds are produced. In addition to the glandular trichomes registered in the literature, we hypothesized that other morphotypes of secretory cells and tissues could be present in M. calabura. In this paper, we analysed the leaf and stem anatomical traits of M. calabura to assess the production sites of bioactive compounds. Leaf and stem samples were collected from plants living in an urban area in Botucatu city, southeastern Brazil, and submitted to standard methods for anatomical and histochemical assessments. The leafblade was hypoestomatic, heterobaric and exhibited dorsiventral mesophyll. The petiole had parenchyma cortex, central vascular system and parenchyma pith. The stem presented parenchyma cortex, peripheral vascular system and parenchyma pith. Druses of calcium occurred mainly in the inner cortex of stem, petiole and midrib. Abundant glandular and non-glandular trichomes characterized the epidermis of leaves and stem. Phenolic compounds and mucilage were detected in the glandular trichome head cells in all the analysed organs, in addition to the cortical cells of midrib, petiole and stem. Voluminous bi-compartmentalized cells containing phenolic compounds and mucilage characterized the epidermis in the adaxial surface of the leaf blade. These cells were a remarkable feature that deserve further investigation. Our results shed light to the poorly known secretory system of M. calabura and proved the occurrence of different morphotypes of secretory cells and tissues in its leaves and stem. The obtained data can guide more studies with ecological, structural and taxonomic approaches, and for researches on drug bioprospecting from this species.